ANALISIS PEMENUHAN KEBUTUHAN INFORMASI PETANI TANAMAN HIAS DALAM UPAYA MENINGKATKAN KUALITAS TANAMAN PADA KOMUNITAS (PAI ) PERHIMPUNAN ANGGREK INDONESIA KABUPATEN TULUNGAGUNG - An'im, Ulul; Budi Juvitasari , Prisca (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
The urgency of this research lies in how the fulfillment of information needs can contribute to improving the quality of cultivated plants. This study aims to examine the fulfillment of information needs by ornamental plant farmers, focusing on the Indonesian Orchid Association community in Tulungagung Regency. The method used is qualitative with a descriptive approach, through data collection techniques, namely observation, in-depth interviews, and documentation. Data analysis is carried out with the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study show that farmers’ information needs are divided into four categories: up-to-date, daily, in-depth, and concise and complete information needs. The media used by ornamental plant farmers, especially orchids, to obtain information include books, social media, YouTube channels, direct discussions in the community, and exchanging ideas with more senior farmers. The choice of media depends on individual preferences and needs, with a strong tendency towards digital media due to ease of access and completeness of information. Farmers are selective about information, by verifying and cross-checking the sources used. The information obtained has been shown to contribute to increasing cultivation efficiency, such as accelerating the growth and flowering of orchid plants. However, there are still obstacles faced by farmers, both internally such as limitations in understanding information, and externally such as limited access to technology and time. These findings are expected to be the basis for formulating strategies to meet relevant and effective information needs for ornamental plant farmers in the digital era.